2019
DOI: 10.1159/000504414
|View full text |Cite
|
Sign up to set email alerts
|

Medication-Induced Repigmentation of Gray Hair: A Systematic Review

Abstract: Hair graying is a common sign of aging resulting from complex regulation of melanogenesis. Currently, there is no medical treatment available for hair repigmentation. In this article we review the literature on medication-induced hair repigmentation, discuss the potential mechanisms of action, and review the quality of the literary data. To date, there have been 27 studies discussing medication-induced gray hair repigmentation, including 6 articles on gray hair repigmentation as a primary objective, notably wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 55 publications
2
30
2
Order By: Relevance
“…Moreover, Pan deficiency results in greying hair in rats and other animals. Studies have shown that vitamin B 5 supplementation with calcium pantothenate can promote grey hair darkening [5]. Neither the toxicity nor the upper intake level have been established [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Pan deficiency results in greying hair in rats and other animals. Studies have shown that vitamin B 5 supplementation with calcium pantothenate can promote grey hair darkening [5]. Neither the toxicity nor the upper intake level have been established [6].…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that complete loss of McSCs or a reduction in their function results in the generation of hair shafts that lack pigment, otherwise known as gray hairs (Harris et al, 2013(Harris et al, , 2018Nishimura et al, 2005). However, in humans, a small but notable number of case reports demonstrate that gray hair can be drastically reversed in response to various systemic medications suggesting that either non-functional McSCs retained in the stem cell niches of gray hairs can be induced to resume their normal function or that functional McSCs can be recruited from neighboring hairs to repopulate niches of gray hairs (Khaled, Trojjets, Zeglaoui, Fazaa, & Kamoun, 2008;Manson, Marabelle, & Houot, 2018;Nagase, Inoue, & Narisawa, 2017;Rivera et al, 2017;Yale, Juhasz, & Atanaskova Mesinkovska, 2020). Regardless of the source of McSCs, the observation that repigmentation of gray hair can occur indicates that the follicular pigment system is physiologically capable for and responsive to pharmacologically induced rejuvenation.…”
mentioning
confidence: 99%
“…1 In a 2020 'systematic review of drug-induced re-pigmentation of grey hair', there were only 27 papers on the subject, of which 6 were full studies with the primary objective of investigating the matter, while the rest were incidental reports. 2 In total, about 130 medications have been implicated. Considering that many medications have been used by millions of patients worldwide, it can be argued that hair re-pigmentation or darkening is an uncommon druginduced event.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that many medications have been used by millions of patients worldwide, it can be argued that hair re-pigmentation or darkening is an uncommon druginduced event. 2 Hair darkening has been linked to psoralen treatment, vitamin supplementation (including vitamin B complex), some antineoplastics (including erlotinib, imatinib, tamoxifen, anti-programmed cell death 1 and anti-programmed cell death ligand 1), retinoids (including etretinate and acitretin), some antiretrovirals, captopril, valproate, ciclosporin, minoxidil, verapamil and levodopa. [2][3][4] Since the 1990s, cholinesterase inhibitors have been used to treat the cognitive manifestations of Alzheimer disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation